2017
DOI: 10.1101/138867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A thermostable Cas9 with increased lifetime in human plasma

Abstract: CRISPR-Cas9 is a powerful technology that has enabled genome editing in a wide range of species. However, the currently developed Cas9 homologs all originate from mesophilic bacteria, making them susceptible to proteolytic degradation and unsuitable for applications requiring function at elevated temperatures. Here, we show that the Cas9 protein from the thermophilic bacterium Geobacillus stearothermophilus (GeoCas9) catalyzes RNA-guided DNA cleavage over a wide temperature range and has an enhanced protein li… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 43 publications
4
51
0
Order By: Relevance
“…To test this idea, we conducted cleavage assays using various type IIC Cas9 orthologs previously shown to function in human cells (Esvelt et al, 2013; Harrington et al, 2017; Hou et al, 2013; Kim et al, 2017). We found that in addition to NmeCas9, the AcrIIC1 from Neisseria meningitidis (AcrIIC1 Nme ) exhibits robust inhibition of the Cas9 proteins from Geobacillus stearothermophilus (GeoCas9) and Campylobacter jejuni (CjeCas9) (Figure 1B and S1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this idea, we conducted cleavage assays using various type IIC Cas9 orthologs previously shown to function in human cells (Esvelt et al, 2013; Harrington et al, 2017; Hou et al, 2013; Kim et al, 2017). We found that in addition to NmeCas9, the AcrIIC1 from Neisseria meningitidis (AcrIIC1 Nme ) exhibits robust inhibition of the Cas9 proteins from Geobacillus stearothermophilus (GeoCas9) and Campylobacter jejuni (CjeCas9) (Figure 1B and S1B).…”
Section: Resultsmentioning
confidence: 99%
“…To determine which region of Cas9 interacts with AcrIIC1, we generated Cas9 truncations and tested their abilities to bind to AcrIIC1 using size exclusion chromatography (Figure 3A, 3B and S3A). Although many NmeCas9 truncations were insoluble, we took advantage of the thermostable GeoCas9 (Harrington et al, 2017) to generate soluble truncations. AcrIIC1 was able to associate with GeoCas9 without either the REC or PAM-interacting domains (Figure 3A), leaving the two nuclease domains as potential interacting partners.…”
Section: Resultsmentioning
confidence: 99%
“…Both the PAMs and the required guide-target base pairing for Type II-C Cas9s are longer than those of other subtypes, which make them inherently more specific (Mir et al, 2018). Genome editing in mammalian cells with three Type II-C Cas9s indeed showed a low off-target activity (Esvelt et al, 2013; Harrington et al, 2017; Hou et al, 2013; Kim et al, 2017; Lee, Cradick, & Bao, 2016). Additionally, many organisms that host Type II-C exist in extreme conditions such as Yellowstone national park acidic hot springs ( Acidothermus cellulolyticus ), pig respiratory tracts ( Pasteurella multocida ), and waste water land from Thailand ( Tisterilla mobilis ), and their Cas9s are stable and suited for genome editing under unusual conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many organisms that host Type II-C exist in extreme conditions such as Yellowstone national park acidic hot springs ( Acidothermus cellulolyticus ), pig respiratory tracts ( Pasteurella multocida ), and waste water land from Thailand ( Tisterilla mobilis ), and their Cas9s are stable and suited for genome editing under unusual conditions. For example, the Type II-C Cas9 from Geobacillus stearothermophilus (GeoCas9) has been shown to have a higher lifetime in human plasma making it a better tool as an RNP to inject in human bloodstream (Harrington et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…There are also other natural CRISPR nucleases with completely different PAM sequences recognition shown to function efficiently in mammalian cells including Campylobacter jejuni ‐derived Cas9 (CjCas9; Kim et al, 2017), Acidaminococcus sp. BV3L6 Cpf1 (AsCpf1) and Lachnospiraceae bacterium ND2006 Cpf1 (LbCpf1; Zetsche et al, 2015), Staphylococcus aureus (SaCas9; Ran et al, 2015), Francisella novicida (FnCas9; H. Hirano et al, 2016), Streptococcus thermophilus Cas9 (StCas9; Müller et al, 2016), Geobacillus stearothermophilus (GeoCas9; Harrington et al, 2017), Neisseria meningitidis Cas9 (NmeCas9; Lee, Cradick, & Bao, 2016), Streptococcus canis (ScCas9; Chatterjee, Jakimo, & Jacobson, 2018). These CRISPR nucleases have extended the targeting range in CRISPR/Cas‐mediated genome editing.…”
Section: Introductionmentioning
confidence: 99%